Editorial: Land rights and responsibilities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
In a world with limited arable land and growing populations, ICTs are increasingly becoming part and parcel of land policy. It´s easy to see why - ICTs offer affordable, efficient means of mapping land boundaries and making land information availabl